ELECTRONICS FEE COLLECTION AND ITS APPLICATION IN VARIOUS EU COUNTRIES - Latislav, Richard; Ondrus, Jan (Doprava a spoje, 2006)
Electronics Fee Collection (EFC) is among priority elements of transport telematics. According to categorization of basic services of ITS (Intelligent Transport Systems) defined by European project KAREN, EFC is the part of financial services and transport control groups, emergency, and demand which is one of the main services in wide portfolio of IDS users needs. Fee collection is a typical transport service highly dependent on identification of vehicle type and position. In my contribution I would like to concentrate on transport performance payments.